Walking gait biomechanics in individuals with quadriceps tendon autograft anterior cruciate ligament reconstruction - Pfile, Kate; Prosser, Bennett; Slone, Harris; McLeod, Michelle; Gregory, Chris; Hunnicutt, Jennifer (Frontiers in Sports and Active Living, 2025)
IntroductionWalking is a vital movement, corresponding to physical activity, health, and independent living. Persistent abnormal lower extremity kinetics and kinematics during walking may influence long-term joint health. Anterior cruciate ligament (ACL) injuries are common sport-related knee joint injuries resulting in short- and long-term dysfunctional movement patterns. Re-establishing normal gait biomechanical patterns following ACL reconstruction (ACLR) is a universal long-term rehabilitative goal and indicator of restored function. The use of the quadriceps tendon (QT) graft technique by orthopedic surgeons is increasing and growing evidence suggests it's viable for ACLR. However, no information is available examining walking gait biomechanics in QT-ACLR patients. Our study evaluated three-dimensional hip and knee joint biomechanics during the stance phase of walking gait in patients with QT-ACLR by comparing the ACLR and nonsurgical limbs. We hypothesized hip and knee joint biomechanics will differ between the QT-ACLR and nonsurgical limbs during the stance phase of gait.MethodsWe recruited a convenience sample of 14 patients with unilateral QT-ACLR ∼11 months post-surgery from an orthopedic surgery clinic. Three-dimensional hip and knee kinematics and kinetics and vertical ground reaction force were assessed while participants walked at self-selected speeds. Data were time-normalized from 0%–100% (% stance phase), and ACLR and nonsurgical limbs were compared using curve analyses with 95% confidence intervals. Cohen's d effect sizes identified clinical differences between limbs.ResultsThe ACLR limb was significantly different from the nonsurgical limb for knee flexion angle (1%–8% and 58%–85%), knee flexion moment (14%–23%), hip flexion moment (60%–67%), knee adduction angle (9%–32%, 92%–100%), knee adduction moment (53%–81%), hip frontal plane angle (0%–100%), hip abduction moment (31%–35% and 71%–76%), knee external rotation angle (0%–100%), knee internal rotation moment (55%–84%), hip transverse plane angle (20%–39% and 88%–100%), and hip internal rotation moment (56%–88%). All significant findings had large effect sizes (d > 0.8).DiscussionThree-dimensional biomechanical gait alterations are present at the knee and hip following QT-ACLR when comparing between limbs. This pattern is consistent with other ACLR graft types. Participants demonstrated gait patterns associated with quadriceps avoidance and reduced proximal forces during the loading response and terminal stance phases. Rehabilitation and functional movement programs should target these deficits.